Optimalisasi Wisata Berbasis Blue Economy melalui Pemberdayaan Masyarakat, Digitalisasi Keuangan, dan Konservasi Terumbu Karang - Yuntini, Kadek; Cahyani, Komang Novia Indah; Putri, Ni Putu Ginanti Ari Kirana; Agustari, Ni Putu Suhaeni Kusuma; Oktaviani, Ketut Widari (JPM: Jurnal Pengabdian Masyarakat, 2026)
The Student Organization Capacity Strengthening Program (PPK Ormawa) initiated by the Economics and Accounting Student Association of Universitas Pendidikan Ganesha was carried out in Penuktukan Village, Tejakula District, Buleleng Regency, Bali, with a focus on a blue economy-based transformation. The village has significant marine tourism potential through coral reefs and diving spots, yet its development remains limited due to low financial literacy, weak institutional capacity, and threats of marine ecosystem degradation. This program aims to empower local communities by strengthening the capacity of tourism awareness groups (Pokdarwis) and marine community surveillance groups (Pokmaswas), promoting digital financial literacy for MSMEs, and supporting coral reef conservation for sustainable tourism management. The partners involved included village authorities, Pokdarwis, Pokmaswas, youth organizations, and local MSMEs. The program was conducted in three phases: preparation (survey, FGD, and needs assessment), implementation (socialization, training, drafting of village regulations, marine conservation, product development and digital marketing, and revitalization of tourism infrastructure), and evaluation (pre-test and post-test, field observation, and feedback questionnaires). The results indicate significant improvement in community awareness, with the average pre-test score of 45.8 increasing to 84.7 in the post-test. Local practices of destructive fishing have decreased, MSMEs adopted digital bookkeeping through the Buku Warung application, and Pokdarwis improved their skills in digital promotion. Furthermore, a village tourism community was established as a platform for continuous education. This program successfully enhanced ecological awareness, social solidarity, and economic independence, contributing to the development of Penuktukan as a sustainable marine tourism destination based on the blue economy approach.